2003
DOI: 10.1167/iovs.02-0819
|View full text |Cite
|
Sign up to set email alerts
|

Methods and Perceptual Thresholds for Short-Term Electrical Stimulation of Human Retina with Microelectrode Arrays

Abstract: Threshold charge densities in severely blind patients were substantially higher than that in a normal-sighted patient. Charge densities in blind patients always exceeded one seemingly reasonable estimate of safe stimulation. The potential adversity of long-term stimulation of the retina by a prosthesis has yet to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
215
4
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 342 publications
(242 citation statements)
references
References 23 publications
19
215
4
4
Order By: Relevance
“…Acute studies have been performed successfully with five patients with RP and one sighted patient. 25,26 A second German epiretinal prosthesis group, Epiret GmbH, has also recently successfully implanted a 25-electrode array (EPIRET3) into six patients over a 4-week period. 23 The implant was tolerated in five eyes with moderate post-operative inflammation, and the position of the implants remained stable until removal.…”
Section: Eyementioning
confidence: 99%
“…Acute studies have been performed successfully with five patients with RP and one sighted patient. 25,26 A second German epiretinal prosthesis group, Epiret GmbH, has also recently successfully implanted a 25-electrode array (EPIRET3) into six patients over a 4-week period. 23 The implant was tolerated in five eyes with moderate post-operative inflammation, and the position of the implants remained stable until removal.…”
Section: Eyementioning
confidence: 99%
“…A phosphene is defined as any visual sensation represented as a spot of light in the visual field caused by methods other than stimulation of the visual system by light. Phosphenes can be elicited by mechanical forces [2], magnetic stimulation [3][4][5] or electrical stimulation [6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, epi-and subretinal implants have been developed [6][7][8][9][10][11][12][13][14][15]. Humayun et al, [6][7][8][9], Mahadevappa et al, [10], Rizzo III et al, [11,12], Klauke et al, [13], Eger et al, [14] and Keserüet al, [15] and recent clinical trials [16,17] have reported that blind patients perceived sensations of spots of light while the retina was electrically stimulated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first type, which is adopted by most of the leading groups, uses an external camera for image acquisition and processing, after which electrical signals are sent to an implanted microelectrode array, which in turn stimulates ganglion cells. (9)(10)(11)(12) The second type of retinal prosthesis uses photodiode arrays directly implanted at the retina of an eye, to provide direct ganglion cell stimulation. (13)(14)(15) The second type is preferred over the first type, since the first type requires additional functionalities, such as image acquisition, data processing and data transmission.…”
Section: Introductionmentioning
confidence: 99%